ANALISIS ELEMEN VISUAL KEMASAN CHIKI SNACK - Nico Yudha Prathama; Dodi Setianto (Jurnal Dimensi Seni Rupa dan Desain, 2015)
Abstract‘The Visual Element Analysis of Chiki Snack Packaging’. Packaging designgraphic elements that differ between products allegedly have differentmarketing purposes. It is interesting authors to analyze graphical elements onthe packaging chiki. Analysis includes elements that differ in packaging design.Designed packaging there are several elements that influence consumers to takeaction that is expected by manufacturers such as color, shape, brand or logo,illustration, typography, and layout. With the election of good packaging designelements and according to the nature of the product can affect potentialcustomers in choosing what products they will buy. In this paper there is anexplanation of packaging design factors, and some examples of good packagingcriteria, and therefore I took the theme "visual Elements Analysis Of PackagingChiki Snack".Abstrak‘Analisis Elemen Visual Kemasan Chiki Snack’. Elemen grafis desainkemasan yang berbeda antara produk disinyalir mempunyai tujuanpemasaran yang berbeda pula. Hal ini menarik penulis untukmenganalisa elemen-elemen grafis pada kemasan chiki. Analisameliputi elemen apa saja yang berbeda dalam desain kemasan. Didesainkemasan terdapat beberapa unsur yang mempengaruhi konsumenuntuk melakukan tindakan yang diharapkan oleh produsen, sepertiwarna, bentuk, merek atau logo, ilustrasi, tipografi, dan tata letak.Dengan adanya pemilihan unsur desain kemasan yang baik dan sesuaidengan sifat produk tersebut dapat mempengaruhi para calonkonsumen dalam memilih produk apa yang mereka akan beli. Dalamjurnal ini terdapat penjelasan faktor-faktor desain kemasan, danbeberapa contoh kriteria kemasan yang baik, maka dari itu sayamengambil tema “Analisis Elemen Visual Kemasan Chiki Snack”.